Potential Evapotranspiration Estimation in the Upper Huaihe River Basin, China. (2016) - Xu, Xianghong; Yu, Meixiu; Lu, Jinli; Liu, Xiaolong
Abstract: The atmospheric evaporative demand, one of principal components in water cycle, its accurate estimation is essential for hydrological simulation and forecasting. The purpose of this paper was to propose a plant-growth based dual-source potential evapotranspiration distributed model and investigate its feasibility with the upper Huaihe River basin (China) above the Xixian station as a case study site. Based on the topography, land-use, hydrological, and meteorological data in the Xixian basin, daily gridded potential evapotranspiration was calculated by the newly-build dual-source potential evapotranspiration model during 2000-2010. The relationship between potential evapotranspiration and pan evaporation at different time scales was investigated thereafter. The result revealed that the newly-built model could capture the temporal and spatial variation patterns of potential evapotranspiration moderately well in the upper Huaihe River basin. The analysis of this study also showed that the correlation between potential evapotranspiration and pan evaporation observations at daily, monthly and seasonal scales was affected together by underlying conditions that include, elevation, seasonality and precipitation.